Medication consumption in a Brazilian area covered by the Family Health Strategy: Prevalence and associated factors - Letícia Silveira Goulart; Ingrid Jordana Ribeiro Dourado; Alyna Araújo e Marcondes; Aline Marques; Franciane Rocha de Faria; Débora Aparecida da Silva Santos (Universidade Federal do Rio de Janeiro, 2019)
Abstract Objective: The aim of the present study was to determine the prevalence and factors associated with the medication consumption among users registered in the Family Health Strategy (FHS) of Rondonópolis, Mato Grosso State, Brazil. Method: The population was constituted of all adult residents in the area covered by the FHS. The Poisson regression model with robust variance was used to the statistical analysis. Results: There were included 553 participants, of which 72% were women. The mean age was 48 years. The prevalence of medication consumption was about 74.9% (n = 414). The most consumed class medication was drugs that act on the cardiovascular system (42.2%). The factors associated with medication consumption were female gender (PR = 1.21; CI95%: 1.07 - 1.38), diagnosed morbidity (PR = 1.83; CI95%: 1.61 - 2.08) and be bedridden in the last month (PR = 1.14; 95% CI95%: 1.02 - 1.26). Moreover, 72.7% of the interviewees obtained the medicines in public pharmacies. Conclusion and implications for practice: Women, people diagnosed with morbidities and those participants who were bedridden during the last month showed the highest levels of drug consumption. Nursing professionals in promoting the rational use of medications can contribute to integral care to FHS users.